Moral Value and Character Education in the "Cars" Movie - Anabella Rosalina Purba; Nidya Ayu Ningtias; Lulu Sepiani Ginting; Merry Susanty Tarigan; Elita Modesta Br Sembiring (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Cars is a film that tells about the life of a racer named Lightning McQueen who has big ambitions to win the prestigious racing event, the Piston Cup. Apart from being an entertainment medium, Film Cars has moral values and character education in it. The aim of this research are to (1) analyze the movie Cars to find out the moral values and character education contained in it, (2) also want to know the relevance of the moral values and character education of class X students to the film Cars. The method used in this research is a descriptive qualitative method, with mobile phones, laptop as research instruments, and materials such as, journals, and books as references. After the data was analyzed, it was found that the car movie actually has moral values like honesty, tolerance, fairness, wisedom, discipline, compassion, helpfulness, courage, cooperation, and democratic. It also has character educations such as honesty, tolerance, hard work, curiosity, respect of achievement, love for the homeland, love of peace, social care, sociable/talkative, responsibility. The relevance of Cars movie to the moral values and character education of students can be seen from each student, and its application in everyday life.